2023
DOI: 10.1038/s41420-023-01474-2
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection causes periodontal fibrotic pathogenesis through deregulating mitochondrial beta-oxidation

Abstract: The global high prevalence of COVID-19 is a major challenge for health professionals and patients. SARS-CoV-2 virus has four structural protein components: the spike protein, envelope protein, membrane protein, and nucleocapsid protein. The SARS-CoV-2 virus mutates predominantly in the spike proteins, whilst the other key viral components usually remain stable. Essentially the pathological functions of the SARS-CoV-2 virus on different cell types are still largely unknown. Previous studies have shown that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has also been shown that SARS-CoV-2 is present in the gingival sulcus [ 19 ] in detectable numbers high enough to be utilized as a reliable diagnostic test. Furthermore, there have been findings regarding the direct pathosis caused by SARS-CoV-2 in the periodontium, including direct fibroblast degeneration and senescence, hyperproliferation, and pathogenic fibrotic phenotypes [ 66 ]. Periodontitis can affect COVID-19 as well, with emerging evidence showing an association between the two diseases [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that SARS-CoV-2 is present in the gingival sulcus [ 19 ] in detectable numbers high enough to be utilized as a reliable diagnostic test. Furthermore, there have been findings regarding the direct pathosis caused by SARS-CoV-2 in the periodontium, including direct fibroblast degeneration and senescence, hyperproliferation, and pathogenic fibrotic phenotypes [ 66 ]. Periodontitis can affect COVID-19 as well, with emerging evidence showing an association between the two diseases [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%